Determination of Self-Efficacy Level: The Capacity of Patients with Hypertension to Manage their Chronic Disease: Penentuan Tingkat Efikasi Diri: Kapasitas Pasien Hipertensi untuk Mengelola Penyakit Kronisnya - Abbass, Zahraa; Jassim, Saja Kareem; AL-Fayyadh, Sadeq; Hafedh, Sukaina; Tiryag, Ali Malik; AL-Hadrawi, Hayder Hamzah Ali (Indonesian Journal on Health Science and Medicine, 2024)
Background: One psychological idea frequently connected to treating chronic illnesses, such as hypertension, is self-efficacy. The objective of this study was to evaluate the ability of hypertensive patients to manage their chronic condition and to determine the link between participants' socio-demographic factors and their self-efficacy in controlling hypertension. Methods: A correlational descriptive design was implemented from October 2022 to March 2024. The study sample was purposive (non-probability), consisting of 171 patients with hypertension. Data were gathered via a Google Form, which includes a socio-demographic data section and the Self-Efficacy for Managing Chronic Disease 6-Item Scale (SES6C). Results: A modest level of self-efficacy among hypertension patients was statistically validated, including 58% of the study population. Equally important, a statistically significant inverse association exists between participants' age and their self-efficacy in controlling hypertension (r = -.250 at p = 0.01). Furthermore, a statistically significant disparity exists in the self-efficacy of hypertension management across gender groups (p-value = .041), age categories (p-value = .000), reading groups (p-value = .032), marital status categories (p-value = .000), follow-up groups (p-value = .000), and exercise groups (p-value = .000). Conclusion: The study's findings indicate a statistically significant difference and link between socio-demographic variables and self-efficacy in treating hypertension. This indicates that self-efficacy in controlling hypertension is a multifaceted notion, and a singular component cannot dictate its trajectory. It is, instead, a result of the interplay of various elements, such as age, gender, experience, and education. Highlights: Assess socio-demographic factors' impact on self-efficacy in hypertension management. Correlational design with 171 hypertensive patients via SES6C scale. Self-efficacy in hypertension control is influenced by diverse socio-demographic factors. Keywords: Self-Efficacy, Hypertension, Chronic Disease, Capacity, Patients